Investigation of certain miRNA expression levels in bovine mastitis cases caused by Escherichia coli and Coagulase-Negative Staphylococci - Behnoush Khasheii; Pezhman Mahmoodi; Taghi Zahraei Salehi; Abdolmajid Mohammadzadeh; Ali Sadeghi-nasab; Morteza Yavari (PLoS ONE, 2026)
MicroRNAs (miRNAs) are small, non-coding RNA molecules approximately 18–25 nucleotides in length that function as essential regulators in numerous biological processes, including immune system function and inflammatory conditions such as bovine mastitis. They hold considerable potential as biomarkers for this disease. This study aimed to investigate the expression levels of inflammation-associated miRNAs in the milk of cows with clinical and subclinical mastitis. In this study, 15 whole milk samples were collected from dairy cows, comprising three groups: clinical mastitis (N = 5), subclinical mastitis (N = 5), and healthy (N = 5). The expression levels of nine inflammation-related miRNAs (miR-146a, miR-92a, miR-155, miR-383, miR-29B-2, miR-223, miR-148a, miR-200a, and miR-205) were measured and analyzed using real-time quantitative PCR (qPCR). The results revealed a significant upregulation in the expression levels of miR-92a, miR-155, miR-223, and miR-200a in clinical mastitis cases induced by Escherichia coli infection. In contrast, subclinical mastitis caused by coagulase-negativestaphylococci (CoNS) showed a significant downregulation of miR-146a, miR-92a, miR-148a, and miR-205. Furthermore, the expression levels of miR-223 and miR-200a were significantly upregulated in both clinical and subclinical forms of the disease. The findings of this study revealed significant alterations in the expression levels of miR-223 and miR-200a, particularly in clinical mastitis, which highlights greater discriminatory power of these miRNAs as diagnostic biomarkers. Accordingly, milk miRNAs appear to have considerable potential for use as non-invasive biomarkers in the early and differential diagnosis of mastitis.